More Than Selection Effects: Volunteering Is Associated With Benefits in Cognitive Functioning. (22nd July 2020) - Kail, Ben Lennox; Carr, Dawn C
Abstract: Objectives: Volunteering is a lifestyle behavior that bolsters cognitive resilience. However, previous studies have not assessed the degree to which cognitive functioning is predictive of becoming a volunteer (i.e., selection into volunteering), and how this might contribute to the superior cognitive performance observed among volunteers. The purpose of this brief report is to address the role of cognition-related selection into becoming a volunteer in the association between formal volunteering and two cognitive measures: (a) overall cognitive function and (b) self-rated memory. Method: The Health and Retirement Study was used to assess whether, net of cognitive selection into volunteering, formal volunteering is associated with cognitive function. Results: Selection explained between 4.9% and 29% of the effect of volunteering on cognitive function (depending on the cognitive outcome and the level of volunteering). However, net of cognitive selection into volunteering, among all cognitive measures there are beneficial effects of formal volunteering on cognitive function. Discussion: These findings suggest a proportion of the positive association between volunteering and cognitive function is explained by selection. However, net of selection, formal volunteering is associated with benefits to cognitive function. These findings offer promise for the development of volunteer-based interventions designed to bolster cognitive functioning.